PEMIKIRAN TEOLOGI MUHAMMAD BIN ABDUL WAHAB DAN PENGARUHNYA DALAM DUNIA ISLAM - Wulandari, Andi Ulfa (Aqidah-ta: Jurnal Ilmu Aqidah, 2023)
Muslims have experienced political, social, economic, and religious attitudes that were increasingly weakened and experienced a setback in the Middle Ages, especially in the Arab region. so that it caused a reaction for Islamic figures to carry out reform movements such as in the fields of politics, science, and religion. Muhammad bin Abdul Wahab, as one of these figures, tried to carry out reforms because he saw the condition of Muslims, especially Arabs, who had made many deviations. This paper focuses on Muhammad bin Abdul Wahab's theological thoughts and his influence on the development of the Islamic world. This study uses a descriptive method with a literature study, namely studying and analysing data related to the thoughts of Muhammad bin Abdul Wahab. Based on this research, it can be concluded that Muhammad bin Abdul Wahab received considerable influence from Ibn Taimiyah and the Hambali school of thought. The renewal movement emphasises the purification of aqidah by avoiding all forms of taklid, bid'ah, and superstition. His thoughts are widespread not only in Arab lands but also in several Islamic areas, including Indonesia.